A 3-dimensional Bergman Kernel method with applications to rectangular domains - Bock, S. (2006)
In this paper we revisit the so-called Bergman kernel method - BKM - for solving conformal mapping problems and propose a generalized BKM-approach to extend the theory to 3-dimensional mapping problems. A special software package for quaternions was developed for the numerical experiments.